Implementasi Sistem Penjaminan Mutu Internal Dalam Meningkatkan Mutu Pendidikan Dasar - Mabruroh, Ani (CV. Kalimasada Group, 2024)
Internal quality assurance is implemented by referring to national education standards, to realize national education goals. Internal quality is now not only applied in universities but also in primary and secondary education. So that quality assurance and fulfillment of education quality standards in primary and secondary education units are more guaranteed and focused. The purpose of this study is to determine and describe the implementation of the Internal Quality Assurance System cycle. The techniques used in data collection are observation, interviews, and documentation studies. The results of this study indicate that the quality improvement activities implemented in accordance with the stages of the SPMI cycle carried out at SMP Al Fadllu include: one, school self-evaluation based on education quality report cards, second, quality improvement planning by establishing a quality assurance committee and re-analyzing the results of the school self-evaluation, third, implementation of quality improvement, fourth, monitoring evaluation and quality improvement results after quality improvement is carried out, and fifth, quality planning again for the following year. The results of the implementation of internal quality assurance have an impact on more innovative learning processes, student achievement and school achievement, customer satisfaction both internally and externally, and the fulfillment of eight national education standards.